2020
DOI: 10.1038/s41419-020-2419-y
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy inhibition potentiates the anti-EMT effects of alteronol through TGF-β/Smad3 signaling in melanoma cells

Abstract: Accumulating evidence demonstrated that alteronol, a novel compound that has a similar structure with paclitaxel, exerts anticancer effects against diversified tumors. However, whether alteronol induces autophagy and the relationship between its anticancer effects and autophagy in melanoma remains elusive. In this study, we show that alteronol induces not only anti-proliferation activity and apoptosis but also autophagy in A375 and UACC62 cells. In addition, alteronol inhibits A375 and UACC62 cells invasion an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 30 publications
2
40
0
Order By: Relevance
“…An important point which is commonly neglected in numerous studies, is that 3-MA may also have an impact on RSV-induced apoptosis in A549 cells. Some studies have demonstrated that 3-MA pre-treatment led to a marked decrease in apoptosis (56,57), while in other cases 3-MA led to an increase in apoptosis (58,59). Additionally, certain studies have demonstrated that 3-MA does not cause an obvious change in the apoptotic cell population in a certain range of time and concentration (60,61).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An important point which is commonly neglected in numerous studies, is that 3-MA may also have an impact on RSV-induced apoptosis in A549 cells. Some studies have demonstrated that 3-MA pre-treatment led to a marked decrease in apoptosis (56,57), while in other cases 3-MA led to an increase in apoptosis (58,59). Additionally, certain studies have demonstrated that 3-MA does not cause an obvious change in the apoptotic cell population in a certain range of time and concentration (60,61).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the interplay between apoptosis and autophagy is complex and highly dependent on the cellular context and different treatments. Under certain circumstances, autophagy inhibits apoptosis or the activation of apoptosis is coupled to the suppression of autophagy (59,62), whereas in other instances, it acts synergistically with apoptosis and is even considered an upstream event of apoptosis (57,63). It also has been found that licochalcone A-induced autophagy is neither pro-nor anti-apoptotic (64).…”
Section: Discussionmentioning
confidence: 99%
“…In prostate cancer, gene chip sequencing revealed the downregulation of smad3 expression after PlncRNA-1 interference. In bladder cancer, PlncRNA-1 regulates cell migration and invasion, whereas smad3 promotes the EMT of tumor cells 51,52 . Furthermore, FISH revealed that PlncRNA-1 is mainly located in the nucleus and partly in the cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…Ultimate evidence has indicated that autophagy activation could rather induce a reversion of the EMT phenotype and several anticancer compounds that induce autophagy also inhibit EMT ( Table 2) (37,(122)(123)(124)(125)(126)(127)(128)(129)135). By its dual role in cancer, the effect of autophagy on EMT appears controversial and likely dependent on the cellular type and/or stage of tumor progression (130)(131)(132)(133)(134). Thus, at early stages of metastasis, autophagy could inhibit the EMT program mainly by destabilizing EMT crucial players.…”
Section: The Effects Of Autophagy On Epithelial-to-mesenchymal Transimentioning
confidence: 99%